Pengaruh RELAKSASI BENSON TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI USIA PRODUKTIF DI WILAYAH KERJA PUSKESMAS PANDANWANGI KOTA MALANG - Harum Rosa KDP; Ekowati Retnaningtyas; Rudi Hamarno Poltekkes (Poltekkes Kemenkes Malang, 2020)
The high case of hypertension is of particular concern in its handling. Benson relaxation therapy is one of the non-pharmacological treatments to reduce blood pressure. The purpose of this study was to see the effect of Benson relaxation on blood pressure of hypertensive patients with productive age. This study used a pre-experimental research design with a design of one group pre-post test design. The sampling technique used was purposive sampling with the number of respondents 30 people formed by a group pre-post test design. All data were processed using SPSS and tested statistically using paired sample t-test which obtained the results of systolic blood pressure before and after 0,000 and diastolic blood pressure results before and after 0,000. The results of the difference between pre and post systolic and diastolic blood pressure showed that benson relaxation therapy had a systolic difference of 9.4 mmHg and diastolic 9.8 mmHg. Thus benson relaxation therapy can be an alternative in the treatment of hypertension. Keywords: Benson Relaxation, Blood Pressure, Hypertension